Examining the Mediating Role of Organisational Support on the Relationship Between Organisational Cynicism and Turnover Intention in Technology Firms in Istanbul - Cicek, Berat; Turkmenoglu, Mehmet Ali; Ozbilgin, Mustafa (Frontiers in Psychology, 2021)
Cynicism and turnover intentions are highlighted as being detrimental to organisations' sustainability. Drawing on the social exchange theory, this paper aims to examine the effect of organisational cynicism on turnover intention and the mediating role of organisational support on this relationship. A survey was conducted with 289 employees and managers. Data were gathered from 54 technology firms from Istanbul, Turkey, and analysed through structural equation modelling using AMOS. The findings suggest that the cognitive and affective dimensions of cynicism are significant predictors of turnover intention, and further that organisational support mediates the relationship between the cognitive and affective dimensions of cynicism and turnover intention. This research is novel in that it deepens our understanding of how detrimental workplace perceptions might affect employees' intentions to leave their organisations and to what extent organisational support mediates this relationship in technology firms in Istanbul, Turkey. To our knowledge, no study has investigated these three variables together, as in the proposed model.